2022
DOI: 10.1093/eurheartjsupp/suac121.159
|View full text |Cite
|
Sign up to set email alerts
|

622 Appropriateness of Echocardiographic Requests for Diagnosis of Infective Endocarditis. A Retrospective Single-Center Study.

Abstract: Background Transthoracic echocardiography (TTE) is the first cardiac imaging modality generally requested for diagnosis of suspected infective endocarditis (IE), while transesophageal echocardiography (TEE) can be performed as initial or supplemental test. Although IE is a relatively rare disease characterized by high mortality, the number of daily in-hospital TTE and TEE requests to diagnose this disease is high, probably because of inappropriate prescriptions. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…8 Most echocardiography requests for diagnosis of infective endocarditis were inappropriate, especially TTE requests, with no signicant impact of the 2017 international guidelines on appropriateness for cardiac imaging in valvular heart disease. 9 TTE is often useful and appropriate for patients in internal medicine https://doi.org/10.37762/jgmds.11-2.577 departments, but its use should be based on clinical indications and not on a cardiologist's preference. 10 A careful review of the available literature showed that no local study was undertaken to evaluate this important tool's usefulness in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…8 Most echocardiography requests for diagnosis of infective endocarditis were inappropriate, especially TTE requests, with no signicant impact of the 2017 international guidelines on appropriateness for cardiac imaging in valvular heart disease. 9 TTE is often useful and appropriate for patients in internal medicine https://doi.org/10.37762/jgmds.11-2.577 departments, but its use should be based on clinical indications and not on a cardiologist's preference. 10 A careful review of the available literature showed that no local study was undertaken to evaluate this important tool's usefulness in clinical practice.…”
Section: Introductionmentioning
confidence: 99%